Oil wealth and insurgency in Nigeria - Adunbi, Omolade (Indiana University Press, 2015)
Omolade Adunbi investigates the myths behind competing claims to oil wealth in Nigeria's Niger Delta. Looking at ownership of natural resources, oil extraction practices, government control over oil resources, and discourse about oil, Adunbi shows how symbolic claims have created an "oil citizenship." He explores the ways NGOs, militant groups, and community organizers invoke an ancestral promise to defend land disputes, justify disruptive actions, or organize against oil corporations. Policies to control the abundant resources have increased contestations over wealth, transformed the relationship of people to their environment, and produced unique forms of power, governance, and belonging.